Sulfur nano-confinement in hierarchically porous jute derived activated carbon towards high-performance supercapacitor: Experimental and theoretical insights. (1st December 2022) - Shah, Syed Shaheen; Aziz, Md. Abdul; Cevik, Emre; Ali, Muhammad; Gunday, Seyda T.; Bozkurt, Ayhan; Yamani, Zain H.
Abstract: High-performance supercapacitors with excellent electrochemical activity require facile and scalable synthesis of electrode materials to fabricate the devices. The synthesis of sulfur-doped activated carbon (AC) has been found to be a suitable route for producing efficient supercapacitor electrodes with high specific energy and specific power combined with low self-discharging. We demonstrate a novel strategy for fabricating S-doped hierarchically porous jute-derived AC nanosheets (S-doped JAC), incorporating the advantages of well-defined hierarchically porous nanosheets morphology of AC and a proper heteroatom modification. It exhibits excellent electrochemical performance, providing high specific capacitance (230 F/g) at a current density of 1.0 A/g in a glycerol-KOH bio-based electrolyte. The symmetric supercapacitor also demonstrates superior specific energy of 32 Wh/kg at a specific power of 500 W/kg, and has excellent cyclic performance with ∼94 % capacitance retention and ∼86 % Coulombic efficiency after 10, 000 charge-discharge cycles. Furthermore, density functional theory was used to calculate the charge density and quantum capacitance to verify the experimental outputs and open up new avenues to prepare high-performance electrochemical energy storage devices. Graphical abstract: Unlabelled Image Highlights: We introduce a novel strategy for the preparation of sulfur-doped carbon materials The S-doped carbon-based supercapacitor exhibit a high specific capacitance of 230 F/g in glycerol-KOH bio-based electrolyte S-doped JAC based symmetric supercapacitor exhibits stable cyclability showing ∼94% capacitance retention for 10, 000 cycles Quantum capacitances of the S-doped carbon materials were calculated from DFT calculations